PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK LAMER PADA MALL METRO PACIFIC PLACE - Lucy Nancy `Simatupang; Bernadet Kuswinar (Jurnal Manajemen, 2017)
The problem in this study wanted to find out the factors that can influence about quality of the product, price, promotion for purchasing decisions of customers in buying cosmetics Lamer at the Metro Mall Pacific Place. The data collected using the formula Roscoe with spread 80 respondents which is Lamer cosmetics customers. Metodology this research is causal relations with test validity, reliability test, test, test the classical asumption corelletion, multiple linear regression, t-test, F-test, and determinants. Based on the results of research partially known that Product quality( X1), Price (X2), Promotion (X3) decision to purchase cosmetics Lamer. The quality of the Product, Price, Promotion of the simultaneous effect on purchasing decisions.